Photocatalytic Degradation of Organic Pollutants: Mechanisms and Material Innovations - Dr. Raj Kumar Sahu (International Journal of New Media Studies: International Peer Reviewed Scholarly Indexed Journal, 2023)
The rapid increase in industrialization and urbanization has led to the release of large quantities of organic pollutants into water and air, posing serious environmental and health challenges. Conventional treatment methods often fail to completely remove persistent organic contaminantssuch as dyes, pesticides, pharmaceuticals, and phenolic compounds. Photocatalytic degradation has emerged as an effective and sustainable approach for the mineralization of these pollutants using semiconductor materials under light irradiation. This study reviews the fundamental mechanisms and recent material innovations involved in photocatalytic degradation processes. The photocatalytic mechanism generally involves photon absorption, generation of electron–hole pairs, charge separation, and formation of highly reactive species such as hydroxyl radicals (•OH) and superoxide radicals (O₂•⁻), which oxidize organic molecules into harmless end products like CO₂ and H₂O.